(untitled) (Philological Studies, 2019)
The main aim of this paper is to show in which role and how the characters of the old men can appear. This research was conducted on the material of Viennese edition of Vuk`s collections (SNP II–IV), the State Edition (SNP VI– IX), as well as records of Vuk and his associates from the so called manuscript edition (SNPr II–IV).1 Тhe epic stylization оf an old hero was monitored in a diachronic perspective, in consultation of Bogišić`s (Bogišić, 2003) and Pantić`s (Pantić, 2002) collections, and the Erlangen manuscript (ER). The comparativetypological and structural-semiotic methods were functionalized for the purpose of this research. The research shows that the old man in epic emerges in two ways – from a typical to atypical – either as an honorable elder, supreme authority and wise man, i.e. „old wolf“, or as power-hungry weakling, with inappropriate materialistic or sexual appetites – on the negative characterization scale. The different mythical, ritual and social elements, assimilated in the notion of community about a certain historical epoch where the characters are situated in and the procedures of epic stylization build some of the most recognizable figures in Serbian oral poetic gallery which reveal full complexity and „layering structure“ of the epic characters of the old men.